Determinants of Employee Retention in Nepalese Financial Institutions - Thapa, Makshindra; Shrestha, Prakash (The Batuk, 2025)
The issue of employee retention is crucial in Nepalese financial institutions. In this regard, this study aims to analyze the effect of compensation, career development, work-life balance, work environment, team dynamics, and leadership and management on employee retention. The casual comparative design was applied and primary data was collected through a questionnaire survey on a sample of 308 employees working in Nepalese financial institutions. Descriptive statistics, correlation analysis, and regression analysis were the statistical tools used. The empirical findings of regression analysis indicated mixed effects of the determinants used to predict employee retention. The result has shown that compensation, career development, and team dynamics have a positive and significant impact on employee retention. In contrast, work environment, work-life balance, and leadership and management have no significant effect on employee retention. The study has revealed some areas important to retain skilled and experienced employees and achieve competitive benefits by Nepalese financial institutions.